FREQUENCY AND SEVERITY OF NEUTROPENIA IN DIFFUSE LARGE B-CELL NON HODGKIN'S LYMPHOMA AFTER FIRST CYCLE OF CHEMOTHERAPY COMPRISING CYCLOPHOSPHAMIDE, DOXORUBICIN, VINCRISTINE WITH PREDNISOLON - Nadeem, Mohammad; Idrees, Muhammad; Khattak, Javeed; Hussain, Iftikhar; Amin, Zulfiqar; Arif, Salman; Zeeshan, Mansoor; Hussain, Mussavir (Journal of Ayub Medical College Abbottabad, 2011)
Background: Chemotherapy used for malignant diseases may produce severe neutropenia in first cycle which may compel for dose modification and early termination of therapy. This descriptive cross sectional study was planned to see the frequency and severity of neutropenia after first cycle of chemotherapy comprising cyclophosphamide, doxorubicin, vincristine with prednisolon in patients of diffuse large B-cell non Hodgkin's lymphoma presenting at Oncology Department Combined Military Hospital Rawalpindi from August 2009 to July 2010. Methods: Thirty patients of diffuse large B-cell non Hodgkin's lymphoma diagnosed on lymph node biopsy presenting for the first time at Oncology Department Combined Military Hospital Rawalpindi were included. They were admitted in the ward and evaluated with history, physical examination and staging investigations. Patients were then planned for first cycle of chemotherapy comprising cyclophosphamide, doxorubicin, and vincristine with prednisolon. After the first cycle of chemotherapy they were monitored for expected neutropenia in the ward. The neutrophil counts were repeated on days 7 and 10 following chemotherapy. Neutropenia was graded as defined in the operational definition and all the data was entered on a specially designed data card. Results: As much as 3.3% of patients suffered from grade IV neutropenia (absolute neutrophil count of <0.5×109/L), 3.3% had grade III neutropenia (absolute neutrophil count of 0.5×109/L- 0.9×109/L), 6.6% had Grade II neutropenia (absolute neutrophil count 1.0×109/L-1.4×109/L and 10% had Grade I neutropenia (absolute neutrophil count 1.5×109/L-1.9×109/L. Conclusion: Overall 23.2% suffered from neutropenia of all grades post 1st cycle of chemotherapy comprising cyclophosphamide, doxorubicin, vincristine with prednisolon in diffuse large B-cell non Hodgkin's lymphoma. Further studies are required to find the risk factors to predict this complication in our population. Keywords: Non Hodgkin's lymphoma, CHOP chemotherapy, Neutropenia